Rituximab-induced Cytokine Storm in the Absence of Overt Lymphoproliferative Disease. Issue 1 (January 2016) - Williams, Mark; Khalid, Tasneem; Hughes, Stephen; Bonney, Denise; Wynn, Robert
Abstract : Rituximab is a monoclonal antibody that first demonstrated efficacy in the treatment of lymphoma but has since seen a dramatic growth in its use for other conditions. Cytokine release syndrome (CRS) is a rare but potentially fatal complication of rituximab infusion that has been described in patients with bulky lymphoproliferative disease. Here we report a convincing case of CRS occurring in a patient with no demonstrable lymphoproliferation. This case has implications for our understanding of the pathogenesis of CRS, our attempts to define an at-risk population and the design of future monoclonal antibodies.